Answer:
16
Step-by-step explanation:
to reverse the division meaning the fraction, we multiply 4 by 4:
4 times 4=16
to check, divide:
16/4=4
i hope this helps u pls give a brainliest and a thx ;)
3323.5 because if you times the number left by the 15 percent this is the answer.
a. (f+g)(x) = 8x+2
b. (f-g)(x) = 4x-6
Step-by-step explanation:
Given
![f(x) = 6x-2\\and\\g(x)=2x+4](https://tex.z-dn.net/?f=f%28x%29%20%3D%206x-2%5C%5Cand%5C%5Cg%28x%29%3D2x%2B4)
<u>a. (f+g)(x)</u>
![(f+g)(x)=f(x)+g(x)\\=6x-2+(2x+4)\\=6x-2+2x+4\\=6x+2x-2+4\\=8x+2](https://tex.z-dn.net/?f=%28f%2Bg%29%28x%29%3Df%28x%29%2Bg%28x%29%5C%5C%3D6x-2%2B%282x%2B4%29%5C%5C%3D6x-2%2B2x%2B4%5C%5C%3D6x%2B2x-2%2B4%5C%5C%3D8x%2B2)
<u>b. (f-g)(x)</u>
![(f-g)(x)=f(x)-g(x)\\=(6x-2)-(2x+4)\\=6x-2-2x-4\\=6x-2x-2-4\\=4x-6](https://tex.z-dn.net/?f=%28f-g%29%28x%29%3Df%28x%29-g%28x%29%5C%5C%3D%286x-2%29-%282x%2B4%29%5C%5C%3D6x-2-2x-4%5C%5C%3D6x-2x-2-4%5C%5C%3D4x-6)
Hence,
a. (f+g)(x) = 8x+2
b. (f-g)(x) = 4x-6
Keywords: Functions
Learn more about functions at:
#LearnwithBrainly
Answer:
D. -14
Step-by-step explanation: